2023
DOI: 10.31413/nativa.v11i1.14394
|View full text |Cite
|
Sign up to set email alerts
|

CLONAL MICROPLANT PRODUCTION, MORPHOLOGICAL EVALUATION AND GENETIC STABILITY OF Dendrocalamus asper (Schult. & Schult.) Backer ex. K. Heyneke

Abstract: Bamboo species have many commercial applications, considering that homogeneous plantations (formed from clonal plants) are essential to high sustainable biomass production. The cloning of selected plants on an industrial scale through in vitro cultivation has many advantages, being important for the supply of plants in sufficient quantity and quality to meet commercial demand. The control of the cloning is the basis for an industrial scale, and its knowledge can optimize the process. This work aimed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Aseptic in vitro cultures of D. asper were started from nodal explants in MS media containing BAP (2 mg·L −1 ) as described in previous study [ 5 ]. Previously synthesized and characterized citrate-AuNPs and CTAB-AuNPs were used in the present study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aseptic in vitro cultures of D. asper were started from nodal explants in MS media containing BAP (2 mg·L −1 ) as described in previous study [ 5 ]. Previously synthesized and characterized citrate-AuNPs and CTAB-AuNPs were used in the present study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…MS media supplemented with benzyladenine (BAP; 2 mg•L −1 ), kinetin (1 mg•L −1 ) and Naphthalene acetic acid (NAA; 0.5 mg•L −1 ) optimally induces callus formation and organogenesis [4]. Gonçalves et al, 2023 [5] reported that MS media supplemented with 2-3 mg•L −1 BAP and 4 mg•L −1 indole-3-butyric acid (IBA) resulted in shoot and root growth, respectively. Moreover, researchers have used various elicitors, including nano-particles (NPs) with various physical and chemical properties, to increase in vitro calli and shoot proliferation [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%